Village Road Geometric Design Using AutoCAD® CIVIL 3D: The Case of Majalengka, Indonesia - Renaldi Agustian; Andri Irfan Rifai; Arief Rijaluddin; Joewono Prasetijo (Engineering Proceedings)
The latest technology to support geometric road planning must be implemented properly. Village road design using digital applications is believed to be able to produce the best planning. This paper aims to analyze the geometric planning of village roads using the AutoCAD® Civil 3D application. The data and planning location is on Village Road in Majalengka Regency, Indonesia. The research method used is to digitize manual planning using the AutoCAD application. The planning standard uses a combination of AASHTO and Indonesia Standard. The study results show that using AutoCAD® Civil 3D for village road planning provides convenience, speed, and the best planning precision.